ANALISA EKONOMI USAHATANI PADI DENGAN PESTISIDA ORGANIK URINE SAPI (Studi Kasus di Desa Sopet, Kecamatan Jangkar, Kabupaten Situbondo) - Hendra Ciptadi; Yohanes Nangameka (Program Studi Agribisnis Fakultas Pertanian, 2015)
The aimed to defermine the difference between the revenue and the efficient of cow urine organic pesticides with inorganic pesticides in the village of sopet. Nangger hemlet village distrets sopet jangkar is one of the objects that have a decent area planted with vice by using organic pesticides cow urine and distance with researchers location close enough to the researchers that helps smooth researchers, especially in terms of efficiency an time. The research method used is descriptive method, komparatif, is the systematic description on the facts as well as between fenomina were investigated.Whereas the comparative method is atype of research that is used to compare a variable between different subjects to the test on the presence or absence hepotesa the difference between the variable being examined. Determination of the respondents in the cencus done by takeing the data 23 heads of familly farming rice with organic pesticides cow urine and determination of respondent was conducted by randomly retrieving data 23 heads of rice farming families with inorganic pesticides. Method of data collection is done through observation, cencus and koisoner. With additional types of data in the study of which uses primary and secondary. Hipotesa testing data analysis techaves first by calculating the difference of rice and farm income hypotesis to the two to determine the efficiency of rice farming. The result of the first hypotesa revenves rice farming with cow urine organic pesticides nothing difference in carning after pesticides “ T ” with pesticides inorganic and second yield hepotesa, both are equally efficiency than inorganic pesticides.